Nivolumab plus chemotherapy versus placebo plus chemotherapy in patients with HER2-negative, untreated, unresectable advanced or recurrent gastric or gastro-oesophageal junction cancer (ATTRACTION-4): a randomised, multicentre, double-blind, placebo-controlled, phase 3 trial. Issue 2 (February 2022) - Kang, Yoon-Koo; Chen, Li-Tzong; Ryu, Min-Hee; Oh, Do-Youn; Oh, Sang Cheul; Chung, Hyun Cheol; Lee, Keun-Wook; Omori, Takeshi; Shitara, Kohei; Sakuramoto, Shinichi; Chung, Ik-Joo; Yamaguchi, Kensei; et al.
Summary: Background: The additive or synergistic sustained antitumour effect of immune checkpoint inhibitors in combination with oxaliplatin-based chemotherapy has previously been reported. We investigated the efficacy of nivolumab plus oxaliplatin-based chemotherapy versus placebo plus oxaliplatin-based chemotherapy as first-line therapy for patients with HER2-negative, unresectable advanced or recurrent gastric or gastro-oesophageal junction cancer. Methods: We did a randomised, multicentre, double-blind, placebo-controlled, phase 2–3 trial (ATTRACTION-4) at 130 centres (hospitals, cancer centres, and medical centres) across Japan, South Korea, and Taiwan. We enrolled patients aged 20 years and older with previously untreated (except for neoadjuvant or adjuvant chemotherapy completed ≥180 days before recurrence), HER2-negative, unresectable, advanced or recurrent gastric or gastro-oesophageal junction cancer (regardless of PD-L1 expression), at least one measurable lesion per Response Evaluation Criteria in Solid Tumours guidelines (version 1.1), and a baseline Eastern Cooperative Oncology Group (ECOG) performance status of 0 or 1. Patients were randomly assigned (1:1) to chemotherapy every 3 weeks (intravenous oxaliplatin 130 mg/m 2 on day 1 plus either oral S-1 40 mg/m 2 [SOX] or oral capecitabine 1000 mg/m 2 [CAPOX], twice daily on days 1–14), in addition to either 360 mg nivolumab intravenously every 3 weeks (nivolumab plus chemotherapy group) or placebo (placebo plus chemotherapy group). Randomisation was done using an interactive web response system with block sizes of four and stratified by intensity of PD-L1 expression, ECOG performance status score, disease status, and geographical region. Patients, investigators, and the study sponsor were masked to treatment assignment. The primary endpoints were centrally assessed progression-free survival and overall survival in the intention-to-treat population, which included all randomly assigned patients. Safety was assessed in all patients who received at least one dose of the assigned treatment. This trial is registered with ClinicalTrials.gov, NCT02746796 . Trial recruitment is complete and follow-up is ongoing. Findings: Between March 23, 2017, and May 10, 2018, 724 patients were randomly assigned to treatment: 362 patients to the nivolumab plus chemotherapy group and 362 to the placebo plus chemotherapy group. At the time of data cutoff on Oct 31, 2018, with a median follow-up of 11·6 months (IQR 8·7–14·1), median progression-free survival at a prespecified interim analysis was 10·45 months (95% CI 8·44–14·75) in the nivolumab plus chemotherapy group and 8·34 months (6·97–9·40) in the placebo plus chemotherapy group (hazard ratio [HR] 0·68; 98·51% CI 0·51–0·90; p=0·0007). At the time of data cutoff on Jan 31, 2020, with a median follow-up of 26·6 months (IQR 24·1–29·0), median overall survival at the final analysis was 17·45 months (95% CI 15·67–20·83) in the nivolumab plus chemotherapy group and 17·15 months (15·18–19·65) in the placebo plus chemotherapy group (HR 0·90; 95% CI 0·75–1·08; p=0·26). The most common treatment-related grade 3–4 adverse events were neutrophil count decreased (71 [20%] of 359 patients in the nivolumab plus chemotherapy group vs 57 [16%] of 358 patients in the placebo plus chemotherapy group) and platelet count decreased (34 [9%] vs 33 [9%]). Treatment-related serious adverse events of any grade were observed in 88 (25%) patients in the nivolumab plus chemotherapy group and in 51 (14%) in the placebo plus chemotherapy group, of which the most common was decreased appetite (18 [5%] vs ten [3%]). Six treatment-related deaths occurred: three in the nivolumab plus chemotherapy group (one each of febrile neutropenia, hepatic failure, and sudden death) and three in the placebo plus chemotherapy group (one each of sepsis, haemolytic anaemia, and interstitial lung disease). Interpretation: Nivolumab combined with oxaliplatin-based chemotherapy significantly improved progression-free survival, but not overall survival, in Asian patients with untreated, HER2-negative, unresectable advanced or recurrent gastric or gastro-oesophageal junction cancer, and could potentially be a new first-line treatment option for these patients. Funding: Ono Pharmaceutical and Bristol-Myers Squibb.